Analysis of the legal context in advertising generated by influencers on Instagram - Trelles Villanueva, Alicia; Sarget Tarifa, Marisa; Martín Cárdaba, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The advertising activities carried out by influencers on Instagram are integrated into the content, causing the audience to often be unaware of the persuasive intent. For this reason, the platform has developed specific regulations and governments have created laws that regulate this practice. In the study carried out on the legislation in Spain, the United States, Germany, the United Kingdom and Japan, few differences have been found between countries, some being more restrictive than others. Most of them emphasize the importance of using sufficiently descriptive and clear words adapted to the specific format of the message.